ASSESSMENT OF PACKAGE GRAPHICS AND COLOUR ATTRIBUTES ON CONSUMERS’ BUYING BEHAVIOUR IN KENYA - Kosgei, Betty Jepchirchir; Wanjira, Jane (International Journal of Research -GRANTHAALAYAH, 2018)
Understanding consumer buying behaviour and their preference to product attributes has become a key success factor in contemporary competitive and rapid changing business environment. Consumer is now more discerning and individualistic requiring marketers to gain insights into their buying behaviour especially the attitude they have towards product innovation especially packaging. The general objective of the study was to determine the effect of packaging attributes on consumer’s buying behaviour of packaged foods in Kenya. This paper discusses the research findings on the influence of packaged food graphics and colour attributes on consumers’ buying behaviour in Kenya. The study was supported by the Theory of Reasoned Action, the Howard-Sheth Model and Kano’s Theory of Attractive Quality. Descriptive and explanatory research designs were used and a sample of 385 shoppers from three supermarkets in Nairobi was selected randomly while data was collected using structured questionnaires. The selection of supermarkets was based on judgmental sampling in which location and foot traffic was considered. Data was analysed using descriptive statistics in the form of mean, percentages and standard deviations, and inferential statistics in the form of correlation tests and regression analysis. The study found a statistically significant relationship between the attributes of graphics and colour and consumer’s buying behaviour. The study recommends that food manufacturers understand consumer response to their packages, and integrate the inputs into designing the best packaging styles. This can be achieved by involving consumers in the process of packaging so that the right decisions are made without making any assumption regarding the final packaging of food products. This study is beneficial to new and existing food product manufacturers in coming up with strategies and in development of product packaging. Keywords: Package Graphics, Colour Attributes, Consumers’ Buying Behaviour.